Bibliometric Analysis of Research Trends and Novelties for Pneumonia in Children - Ariyani Lutfitasari; Fitriani Nur Damayanti; Budi Santosa; Lia Mulyanti; Umi Khasanah (Fakultas Ilmu Keperawatan Universitas Indonesia, 2024)
Pneumonia is the leading cause of death among children globally, with most cases occurring in low- and middle-income nations. Pneumonia in children has been thoroughly researched in numerous countries throughout the world. However, no research performed bibliometric analyses of pneumonia in children. This study aims to use a biometric analysis to determine trends in the number of publications, the number of citations, network visualization, overlay visualization, and density visualization concerning the issue of pneumonia in children. This research method employs a systematic review with stages adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flowchart. The highest publication increase occurred in 2020, with a rise of 2,739. The number of citations increases exponentially from year to year. The most cited article is